COGNITIVE PROCESSES: PERCEPTION AND SENSATION - Tojiddinova Laylokhan Shokirovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
Perception is a complex and meaningful mental process compared to sensations, and all mental states, characteristics, properties and knowledge, experiences and skills acquired by the human mind as a whole manifest and participate in reflection. Perception is a somewhat more complex, complete reflection process compared to intuition and consists in reflecting things and events that affect our senses as a whole, that is, as a whole, with all their signs and features. For example, when we see an apple, we perceive its shape, color, taste, smell and variety in general. So, almost all of our senses are involved in the process of perception. Therefore, perception is a much more complex reflection process than intuition. Mental life manifests itself in various phenomena. In mental life, phenomena, mental processes, mental products and mental states are distinguished. A mental process is a natural, consistent change in a mental phenomenon, its transition from one stage or space to another stage or space. Mental products are the result of mental processes. These include subjective mental products in the form of images of sensations and perceptions, imaginations, discussions, concepts. Cognitive phenomena are otherwise called mental, intellectual processes.